The narrator in the novel and (auto)biographical self-writing: fiction and reality at the service of experience - Santos, Darlan Roberto dos (Revista de Letras, 2013)
This article aims to discuss the position of the narrator in contemporary literature, and how experience is portrayed – in admittedly (auto)biographical or fictional texts (even though these may have “traces” of their authors’ experiences). Current Brazilian literature novels will be used as examples, including representatives of what we call “waste memoirs”.